(untitled) (Journal of Shaheed Suhrawardy Medical College, 2019)
This randomized controlled trial was conducted in Department of Physical Medicine and Rehabilitation of Bangabandhu Sheikh Mujib Medical University, Dhaka during the period from March 2014 to August 2014 to evaluate the effect of ultrasound therapy (UST) on patients of carpal tunnel syndrome. Total 110 subjects were participated in this study and they were selected randomly divided in two groups by lottery. Group-A was treated with UST, Exercise, Wrist splint, non steroidal anti inflammatory drugs (NSAIDs) and group-B received Exercise, Wrist splint and NSAIDs. Treatment continued for a period of 6 weeks. Group-A were compared to group B by both Visual Analog Scale (VAS) and Levine Symptom severity scale(LSSS) after 3 weeks and 6weeks of treatment. The result showed mean VAS at pretreatment (W0) in group-A was 6.42 ±1.23 and in group-B was 6.17±0.74. Group-A was 1.82±0.43 and in group-B was 3.1±0.23 in their follow up after 3 weeks (W 3) In Group-A was 1.71(±0.52) and in group-B was 2.52(±0.49) at 2nd follow up (W6) after 6 weeks. Mean LSSSat pretreatment (W0),1st follow up after 3 weeks (W 3), 2nd follow up (W 6) after 6 weeksin group-A was 31.64±1.55, 14.32 ± 2.29 and 14.31 ±1.12 respectively,and in group-B was 31.3±0.74,18.51±0.92and 18.31 ± 0.42 respectively.This study revealed that continuous mode of US therapy with exercise, wrist splint, NSAIDs have better outcome in case of Carpal tunnel syndrome patients. J Shaheed Suhrawardy Med Coll, June 2019, Vol.11(1); 24-27